Development & characterization of sulfonated polyethersulfone membrane for proton exchange membrane fuel cell application - Mohd Aizuddin, Hashim (2010)
Sulfonation process was used to produce ion exchange polymer from a commercial polyethersulfone. Sulfonations were achieved by varying the degree of sulfonation (DS) in reaction time. Water and methanol uptake analysis showed this SPES6 have the potential to use in proton exchange membrane fuel cell application compared to another membrane. Methanol uptake analysis showed Nafion 117 have no potential to use in direct methanol fuel cell application because the tendency of Nafion to swell is very high. FTIR analysis showed that the peak of sulfonic group was appeared at wavelength 1072 to 1074 cm-1. TGA analysis showed that the range temperature that was assigned to the degradation of the polymer main chain at around 400°C.